Small-Sample Machine Learning-Based Prediction of Ignition Delay Times for NH3-H2 blends - Chen Wang; Zhan Si; Yanrong Peng; Tingting Wang; Deguang Liu; Haiqiao Wei; Jiaying Pan; Haizhu Yu; Yao Fu (Fuel, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Apatite geochemistry of granites from the Xiaolonghe Tin deposit, Western Yunnan: Implications for petrogenesis and mineralization - Kun Ge; Xiang Sun; Yong Fu; Yaqi Ye; Yingjie Wang; Xianyi Huang; Xiaobo Si; Mingjun Zheng (Journal of Geochemical Exploration, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Balancing N₂O and NH₃ emissions with maize yield: Investigating the role of alternate drip irrigation and 3,4-dimethylpyrazole phosphate (DMPP) - Junming Liu; Yuanyuan Fu; Le Yang; Zhuanyun Si; Sunusi Amin Abubakar; Huijie Li; Tao Zhou; Ruiqi Ren; Hongchen Li; Peng Li; Bingcheng Si; Yang Gao; et al. (Soil and Tillage Research, 2026)

Enhanced atomic hydrogen utilization on ordered Pd1Cu intermetallic single-atom alloy for electrochemical hydrodechlorination - Juening Fan; Yang Liu; Runze Si; Piao Hu; Zhiming Liang; Yangsu Xie; Fu-Kuo Chiang; Maohong Fan; Huihuang Chen; Zhimin Ao; Bo Yang (Journal of Hazardous Materials, 2026)

Investigation of high-performance proton exchange membrane fuel cells with integrated bipolar/gas diffusion layer structures: Effects of porosity gradient in tetradecahedral lattice flow field on mass transfer and electrochemical reactions - Qingshan Liu; Lixin Chen; Jiakun Si; Kexin Peng; Xiaojing Wang; Geng Luo; Pei Fu; Yong Zhang; Junfeng Wang; Yisong Chen (Chemical Engineering Journal, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Interfacial microenvironment engineering of functionalized MOFs for immobilizing PET hydrolase ICCG to overcome the activity–stability trade–off in efficient PET depolymerization - Xinyu Liu; Zhong Wang; Xuan Jing; Xiaomin Hou; Si-Fu Tang (Bioresource Technology, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Investigation of mass transfer and reaction characteristics in three-dimensional fully morphological channel-ridge type gas distribution zones for proton exchange membrane fuel cells - Qingshan Liu; Kexin Peng; Xiaoyi Liu; Jianuo Liu; Jiaxuan Li; Jiakun Si; Wangfang Yuan; Pei Fu; Yong Zhang; Yisong Chen (Fuel, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Failure Behavior of Deep Tunnels Subjected to TBM-Induced Dynamic Disturbance - Hong-Yuan Fu; Ben-Guo He; Si-Yuan Dou (Rock Mechanics and Rock Engineering, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Three-dimensional ordered mesoporous Co1Mn2Ox composite oxides for highly efficient toluene oxidation: Achieving an optimal balance of adsorption, oxidation, and desorption - Xiaodan Wang; Wenbo Si; Qinyue Wang; Zhenchuan Hu; Cheng Li; Chunrong Xiong; Bingqing Zhang; Xiaoqian Fu; Xiaolei Hu (Journal of Environmental Chemical Engineering, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Biomimetic nanospheres as a therapeutic intervention for disrupting the infection-ischemia cycle in ischemic limbs - Ruihan Wang; Chen Yuan; Minghao Cai; Shan Lu; Jiaxiang Han; Zhongbo Sun; Yuanqing Kan; Bin Gao; Daqiao Guo; Weiguo Fu; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Oxime ester–linked N-phenylphthalimide derivatives as PPO inhibitors: structure–activity relationships, herbicidal activity, crop selectivity, and in silico safety assessment - Xian-Ming Zhang; Yue-Li Zou; Ya Jiang; Si-Yi Yao; Shuang Gao; Li-Xia Zhao; Yu-Long Liu; Ying Fu (Pesticide Biochemistry and Physiology, 2026)

Dual-crosslinked polysaccharide microspheres via glycated collagen and sodium alginate/chitosan for intestine targeted delivery of curcumin in ulcerative colitis treatment - Jing-jing Fu; Si-yi Mei; Yong-qiang Chen; Xiang-yu Fu; Yong-jie Long; Jun-xin Wu; Wen-qiang Cai; Yue-wen Chen (Carbohydrate Polymers, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Development and evaluation of an antisense PCR assay for Toxoplasma gondii detection in domestic cats - Yu-Yuan Li; Shao-Yuan Bai; Hai-Qiong Yu; Li-Zhi Fu; Jia-Fu Zhu; Shi-Jie Fan; Ming Pan; Wei He; Si-Yang Huang (Veterinary Parasitology, 2026)

Interactions of carbon‑nitrogen coupling in the Agro-Pastoral Ecotone of Northern China - Shijun Tu; Wanfa Wang; Cai Li; Yuanbi Yi; Jinfeng Ge; Wenrui Yao; Wenhong Shi; Fu-Jun Yue; Zhongjun Wang; Yulin Qi; Si-Liang Li (CATENA, 2026)

Structural and textural enhancement of oleogels via l-lysine-mediated whey protein cryogel modification - Run-Hao Fu; Ran Feng; Si-jie Wu; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2026)

The preferential fractionation of dissolved organic matter (DOM) by co-precipitation with iron in diverse environmental conditions - Tingcang Hu; Chunmei Chen; Yulin Qi; Pingqing Fu; Si-Liang Li (Journal of Hydrology, 2026)

Interfacial electron modulation in NiCo-LDH/CoFcDCA nanohybrids enables high-performance water and urea electrolysis - Li-Wen Wang; Xuan Jing; Si-Fu Tang (Fuel, 2026)

Photo–biodegradation drives organic matter-mediated carbon–nitrogen–sulfur cycling in the reservoir's surface-layer: A multi-index analysis - Haoyang Wang; Xinyu Lao; Khan M.G. Mostofa; Si-Liang Li; Cong-Qiang Liu; Jie Yuan; Jie Zhang; Fu-Jun Yue (Environmental Research, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Mass transfer in electrochemical advanced oxidation processes: A comprehensive review of characterization, influencing factors, and computational fluid dynamics simulations - Zhen Liu; Hongze Yang; Bangxing Ren; Yu Qin; Yiwei Fu; Mingyang Si; Zhuoyuan Li; Jiahui Zhang; Yao Chen (Journal of Water Process Engineering, 2026)

Automatic detection of equatorial plasma bubbles using deep neural networks - Ting Zhang; Yifu Luo; Bin Zhang; Fang Jiang; Tianfang Wang; Si Xiao; Xuesong Bai; Liping Fu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Dual functionality of phosphates in a micellar casein concentrate: reconstitution enhancement while tailoring acid-induced gel structural properties - Yi-Fang Gao; Si-Yi Han; Hong-Fu Zhao; Ying-Hua Zhang (Food Research International, 2026)

Structural modulation of casein peptide-hydroxytyrosol self-assembled nanocomplexes: Enhanced gastrointestinal stability and in vitro antioxidant activity - Si-Yi Han; Hong-Fu Zhao; Wen-Qi Liang; Ying-Hua Zhang; Zhi-Shen Mu (Food Research International, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Closed-form solution method for mechanical response of isolated-span transmission line after ice shedding based on state discretization - Zhao Yan; Si-yuan Wu; Xing Fu; Hong-nan Li; Hao Li; Zeng-hao Huang (Cold Regions Science and Technology, 2026)

Interpretability-Enhanced Mineral Prospectivity Models: A Synergistic Approach Using Large Language Models, Knowledge Graphs, and Machine Learning - Zhen-Jie Zhang; Zi-Xing Yang; Fu-Yuan Jian; Si-Yuan Ban; Yi-Ming Wang (Mathematical Geosciences, 2026)

Unraveling the mechanism by which Lactiplantibacillus plantarum modulates alfalfa silage quality and antioxidant phytochemical accumulation through integrated microbiome–metabolomics analysis - Yuqian Liu; Ze Wang; Wenting Gou; Jia Fu; Mengxue Liu; Nanyi Zhang; Qiang Si; Hongmei Shang (Animal Feed Science and Technology, 2026)

Polystyrene nanoplastics induce ovarian injury by PI3K-Akt pathway-driven macrophage extracellular trap formation - Yingying Chen; Linli Yang; Yuanyuan Li; Lulu Si; Hanlin Fu; Tianjiao Lai; Ruixia Guo (Environmental Pollution, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Bidirectional coupling between metal droplet cluster and direct current air arc: Numerical analysis and physical mechanisms - Wei Duan; Jing Li; Juncheng Yang; Chongyang Huang; Si Fu; Zhengbo Li; Longhao Zhang; Yue Fu; Yundong Cao (Chemical Engineering Journal, 2025)

DNA-assembled architectures for multi-enzyme cascades in high-performance biosensing - Yu Fu; Miao Zhang; Jiaying An; Qingxiang Zhang; Yujie Yu; Han Zhang; Yuxin Si; Di Zhang; Yuxin Fang (Chemical Engineering Journal, 2025)

Hydrophobic magnetic deep eutectic solvents: An all-in-one platform for fast visualization, removal, recycle and degradation of anionic dyes - Yanshang Kang; Yangrui Si; Qiwen Jin; Ruohan Xu; Yujun Zhong; Yaorui Wang; Yuxiang Fu; Jing Gu; Mingfu Ye; Shuangshou Wang (Analytica Chimica Acta, 2025)

Short-term no-tillage improves soil water retention and maintains soil aeration at high moisture conditions despite reduced macroporosity - Jing Tan; Bingcheng Si; Ying Zhao; Yili Lu; Yuxin Chen; Ning An; Song Li; Weichao Wang; Han Fu; Wei Han; Yanli Yi (Soil and Tillage Research, 2025)

Ginseng stem and leaf extract residue improves antioxidant and immune functions and intestinal microflora in broilers - Wenting Gou; Shaonan Liu; Yuqian Liu; Jia Fu; Wei Yuan; Mengxue Liu; Qiang Si; Nanyi Zhang; Hongmei Shang (Research in Veterinary Science, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Establishment of pollen tube-mediated genetic transformation technique of Primula forbesii - Sitong Fu; Weijia Si; Ying Liu; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Ubiquitin-conjugating enzyme StUBC19 regulates osmotic and salt stress in potato transgenic plants - Xue Fu; Xun Tang; Ning Zhang; Xinyu Ren; Peishan Li; Huaijun Si (Plant Science, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Flavor characterization of aged Citri Reticulatae Pericarpium from core regions: An integrative approach utilizing GC-IMS, GC–MS, E-nose, E-tongue, and chemometrics - Haocheng Liu; Manqin Fu; Jijun Wu; Yuanshan Yu; Weili Si; Yujuan Xu; Jiguo Yang (Food Chemistry, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Temporal trends of the disease burden of renal cell carcinoma from 1992 to 2019 in the US: a population-based analysis - Ruyan Chen; Tian Tang; Jianglong Han; Si Li; Wenmin Liu; Haiyu Deng; Tingting Jian; Zhenming Fu (Cancer Causes & Control, 2025)

The biocontrol effect and mechanism of the marine-derived fungus Epicoccum nigrum against Alternaria alternata, the causal agent of tomato black spot disease - Si-Qi Fu; Fei Cao; Sen Pang; Xiao-Qian Qi; Zhi-Hong Xu; Ya-Hui Zhang; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu (Pesticide Biochemistry and Physiology, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Corrigendum to “Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae” [Aquatic Toxicology, 284 (2025) 107402] - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Design, synthesis, and mechanism study of novel isoquinoline derivatives containing an oxime moiety as antifungal agents - Yanxi Jin; Fu Chen; Ying Long; Jianeng Luo; Si Guo; LuYao Wang; Wei Chen (Molecular Diversity, 2025)

Sources and dynamics of nitrate in groundwater in a crystalline terrain of tropical Sri Lanka based on a dual isotope approach - Charitha Udeshani; Fu-Jun Yue; Yao-Qi Gong; Si-Liang Li; Rohana Chandrajith (Water Research, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Spatial and seasonal variation of groundwater geochemistry in high-grade metamorphic aquifers- implications for CKDu in Sri Lanka - Charitha Udeshani; Fu-Jun Yue; Rohana Chandrajith; Nadeesha Hemali Koralegedara; Si-Liang Li (Journal of Hydrology, 2025)

Coordinating red line policies with water consumption caps in China’s drylands - Bingfang Wu; Zonghan Ma; Xiaoming Feng; Hongwei Zeng; Si Gou; Haitao Li; Jianping Huang; Bojie Fu (Science Bulletin, 2025)

Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

Combined failure mechanism of tripod bucket foundations considering torsion effect - Si-Da Wu; Zhuang Jin; Yin-Fu Jin; Zhen-Yu Yin (Ocean Engineering, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Sulfonamide-linked π-conjugated carbon nitride with enhanced intramolecular carrier generation and transfer for efficient photocatalysis - Jiajun Fu; Si Chen; Xuanhui Lin; Zongrui Li; Zhao Mo; Mingyue Dong; Zhigang Chen; Hui Xu (Journal of Environmental Chemical Engineering, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Mechanisms of urea combined with nitrification inhibitors on prompting cadmium uptake and accumulation in rape (Brassica napus L.) - Li Li; Lin Chen; Xin Fu; Zhong Hu; Qingru Zeng; Xiao Deng; Yang Yang; Si Luo (Plant and Soil, 2025)

The cation/H+ exchanger OsCAX2 is involved in cadmium uptake and contributes to differential grain cadmium accumulation between Indica and Japonica rice - Xiang-Qian Liu; Huan Liu; Meng-Jie Fu; Li-Wen Zhang; Si-Fan Yin; Zhong Tang; Fang-Jie Zhao; Xin-Yuan Huang (Journal of Hazardous Materials, 2025)

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Carbon transfer from land to fluvial networks in a typical karst river-reservoir system - Yongmei Hou; Si-Liang Li; Fu-Jun Yue; Shuai Chen; Xiaolong Liu; Lishan Ran (Water Research, 2025)

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

A potential role for the interaction of Wolbachia surface proteins with the Drosophila microtubulin in maintenance of endosymbiosis and affecting spermiogenesis - Bin Mao; Ying-Ying Wang; Si-Ying Li; Yue Fu; Yun-Li Xiao; Yu-Feng Wang (Journal of Insect Physiology, 2025)

Nonlinear finite element model updating and fourier neural operator for digital twin of reinforced concrete containment vessel under seismic excitations - Si Fu; Chang-Ching Chang; Chawit Kaewnuratchadasorn; Jiaji Wang; Chiun-Lin Wu; Yi-Lung Mo; Thomas T.C. Hsu (Engineering Structures, 2025)

Unravelling nitrate transformation mechanisms in karst catchments through the coupling of high-frequency sensor data and machine learning - Xin Liu; Fu-Jun Yue; Wei Wen Wong; Tian-Li Guo; Si-Liang Li (Water Research, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Metal–organic framework-based SERS chips enable in situ and sensitive detection of dissolved hydrogen sulfide in natural water: Towards a bring-back-chip mode for field analysis - Meiyu Si; Yunqing Wang; Rongchao Mei; Xizhen Zhao; Qi Yuan; Longwen Fu; Yixuan Wu; Abbas Ostovan; Maryam Arabi; Shanshan Wang; Lingxin Chen (Journal of Hazardous Materials, 2024)

High salt-resistant and robust MXene@oleylamine/PET composite nonwoven for efficient and long-term solar desalination - Quanpei Xie; Shengwu Deng; Yong Wen; Yang Yang; Wenjie Fu; Jinxin Liu; Si Cheng (Chemical Engineering Journal, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

High sensitivity of dissolved organic carbon transport during hydrological events in a small subtropical karst catchment - Caiqing Qin; Si-Liang Li; Yiping Wu; Adrian M. Bass; Weijun Luo; Hu Ding; Fu-Jun Yue; Pan Zhang (Science of The Total Environment, 2024)

Intensified O2 activation and lattice O supply at inverse oxide-metal interface for catalytic oxidation reactions: A case study in alcohol oxidation - Kun Liu; Yongbin Sun; Jiaqi Si; Cong Fu; Yushui Bi; Xiaomin Zhao; Guofeng Zhao (Chemical Engineering Journal, 2024)

Enhanced control and efficiency in millimeter-scale composite droplets preparation - Jijie Fu; Kai Mu; Fangsheng Huang; Zhiqiang Zhu; Ting Si (Chemical Engineering Journal, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Improvements in recovery of rare earth elements (REEs) from coal via fluidized-bed combustion: Thermal alteration of REE mineralogy and its impact on element extractability - Biao Fu; Yingfu Si; Yongda Huang; Guorong Xu; Yijun Cao; Chunjie Zhao; Yukun Huang; Renjie Zou; Guangqian Luo; Hong Yao (Chemical Engineering Journal, 2024)

Assessing the impact of rainfall on water quality in a coastal urban river utilizing the environmental fluid dynamics code - Qingqing Sun; Suyun Chang; Jingfu Wang; Jing-An Chen; Caiqing Qin; Weiwei Shi; Wen-Xi Zhang; Yutong Zhang; Fu-Jun Yue; Si-Liang Li (Urban Climate, 2024)

Severe flood modulates the sources and age of dissolved organic carbon in the Yangtze River Estuary - Zhao Liang Chen; Yuanbi Yi; Wenjing Fu; Wenzhao Liang; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; Ding He (Environmental Research, 2024)

Implementation of Viscoelastic Artificial Boundary and Seismic Motion Input Method in Three-Dimensional Discontinuous Deformation Analysis Method - Si-huang Lin; Tao Deng; Lu Zheng; Hong Zhang; Wei Wu; Xiao-dong Fu; Guang-qi Chen (Rock Mechanics and Rock Engineering, 2024)

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

Hemilabile single-atom catalysts facilitating photothermal synergetic catalysis - Yiwei Fu; Kejian Lu; Yi Wang; Yitao Si; Jinwen Shi; Naixu Li; Zhifu Zhou; Maochang Liu (Science Bulletin, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

Elucidation of the dominant factors influencing N2O emission in water-level fluctuation zones in a karst canyon reservoir, southwest China - Sai-Nan Chen; Yongmei Hou; Fu-Jun Yue; Zhifeng Yan; Xiao-Long Liu; Si-Liang Li (Science of The Total Environment, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Cactodera guizhouensis n. sp. (Nematoda: Heteroderinae), a new species of cyst-forming nematode parasitizing potato in Guizhou, China - Chun-Hui Ni; Yu-Jia Xie; Si-Hua Yang; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2024)

Quantifying the contribution of methane diffusion and ebullition from agricultural ditches - Xueqi Niu; Wenxin Wu; Weiwei Shi; Zihuan Fu; Xingxing Han; Si-Liang Li; Zhifeng Yan (Science of The Total Environment, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Evaluation of weak genotoxicity of hydroxychloroquine in human TK6 cells - Xilin Li; Yuan Le; Yuxi Li; Si Chen; Lei Guo; Xin Fu; Mugimane G. Manjanatha; Nan Mei (Toxicology Letters, 2024)

Effects of soil pore structure on gas diffusivity under different land uses: Characterization and modelling - Zihuan Fu; Zhifeng Yan; Si-liang Li (Soil and Tillage Research, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

High-frequency data significantly enhances the prediction ability of point and interval estimation - Xin Liu; Fu-Jun Yue; Tian-Li Guo; Si-Liang Li (Science of The Total Environment, 2024)

Nitrate transformation and source tracking of rivers draining into the Bohai Sea using a multi-tracer approach combined with an optimized Bayesian stable isotope mixing model - Xinwei Ren; Fu-Jun Yue; Jianhui Tang; Cai Li; Si-Liang Li (Journal of Hazardous Materials, 2024)

An ultra-thin nickel electrodeposited stainless steel mesh with superhydrophobic property and high mechanical durability for oil-water separation - Xin Zhang; Chuanbo Hu; Xinye Fu; Si Zhang; Tingzhen Li; Beiyue Ma; Kangning Ren (Journal of Environmental Chemical Engineering, 2024)

Recognition and (semi-)quantitative analysis of REE-bearing minerals in coal using automated scanning electron microscopy - Biao Fu; Guorong Xu; James C. Hower; Yijun Cao; Yukun Huang; Liang Si; Li Xian; Guangqian Luo; Guijian Liu; Guangqing Hu; Hong Yao (International Journal of Coal Geology, 2024)

Terbium doping and energy level modification of zirconium organic frameworks as probes for the improved determination of histamine and visual inspection of food freshness - Hui-Hui Xie; Lei Han; Si-Fu Tang (Food Chemistry, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Spatially heterogeneous shifts in vegetation phenology induced by climate change threaten the integrity of the avian migration network - Jie Wei; Fei Xu; Ella F. Cole; Ben C. Sheldon; Willem F. de Boer; Ben Wielstra; Haohuan Fu; Peng Gong; Yali Si (Global Change Biology, 2024)
Phenological responses to climate change frequently vary among trophic levels, which can result in increasing asynchrony between the peak energy requirements of consumers and the availability of resources. Migratory birds use multiple habitats with seasonal food resources along migration flyways. Spatially heterogeneous climate change could cause the phenology of food availability along the migration flyway to become desynchronized. Such heterogeneous shifts in food phenology could pose a challenge to migratory birds by reducing their opportunity for food availability along the migration path and consequently influencing their survival and reproduction. We develop a novel graph‐based approach to quantify this problem and deploy it to evaluate the condition of the heterogeneous shifts in vegetation phenology for 16 migratory herbivorous waterfowl species in Asia. We show that climate change‐induced heterogeneous shifts in vegetation phenology could cause a 12% loss of migration network integrity on average across all study species. Species that winter at relatively lower latitudes are subjected to a higher loss of integrity in their migration network. These findings highlight the susceptibility of migratory species to climate change. Our proposed methodological framework could be applied to migratory species in general to yield an accurate assessment of the exposure under climate change and help to identify actions for biodiversity conservation in the face of climate‐related risks.

Dynamic N transport and N2O emission during rainfall events in the coastal river - Wen-Xi Zhang; Fu-Jun Yue; Yong Wang; Yun Li; Yun-Chao Lang; Si-Liang Li (Science of The Total Environment, 2023)

Highly efficient degradation of antibiotic residues with reagent-free photoelectro-fenton via hollow fiber gas diffusion electrode - Jibin An; Guoqiang Li; Wantong Si; Wei Chen; Jiahong He; Huixia Feng; Jianyang Chen; Haimei Fu (Chemical Engineering Journal, 2023)

Identification of pancreatic lipase inhibitors from Eucommia ulmoides tea by affinity-ultrafiltration combined UPLC-Orbitrap MS and in vitro validation - Han Huang; Ming-Hao Han; Qi Gu; Jian-Dong Wang; Heng Zhao; Bo-Wen Zhai; Si-Ming Nie; Zhi-Guo Liu; Yu-Jie Fu (Food Chemistry, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Aristolochic alkaloids from Piper macropodum and their anti-inflammatory activities - Chun-Yue Liu; Yong-Fu Lu; Si-Xuan Liu; Yong-Fu Li; Yan Dong; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2023)

Water supply sludge-based ceramsite denitrification filter: Pollutant removal and microbial community characteristics - Cui Liu; Xiao Huang; Jianghua Yu; Wei Si; Yicheng Fu (Journal of Water Process Engineering, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

Occurrences and fates of per- and polyfluoralkyl substances in textile dyeing wastewater along full-scale treatment processes - Yuqian Jia; Chao Shan; Wanyi Fu; Si Wei; Bingcai Pan (Water Research, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Regulation of innate immunity in marine mussel Mytilus coruscus: MicroRNA Mc-novel_miR_196 targets McTLR-like1 molecule to inhibit inflammatory response and apoptosis - Yashu Wu; Xirui Si; Longmei Qiu; Xinglu Chen; Peipei Fu; Isabella Buttino; Baoying Guo; Zhi Liao; Xiaojun Yan; Pengzhi Qi (Fish & Shellfish Immunology, 2023)

hUMSCs Transplantation Regulates AMPK/NR4A1 Signaling Axis to Inhibit Ovarian Fibrosis in POI Rats - Linlu Cui; Hongchu Bao; Wenqian Zhu; Yu Tang; Qianqian Luo; Yaru Si; Qiang Fu; Zhonglin Jiang (Stem Cell Reviews and Reports, 2023)

Dunaliella Ds-26-16 acts as a global regulator to enhance salt tolerance by coordinating multiple responses in Arabidopsis seedlings - Si-Yue Liu; Jin-Ge Xie; Xi-Wen Chen; De-Fu Chen (Planta, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

Source availability and hydrological connectivity determined nitrate-discharge relationships during rainfall events in karst catchment as revealed by high-frequency nitrate sensing - Fu-Jun Yue; Si-Liang Li; Susan Waldron; David M. Oliver; Xi Chen; Pan Li; Tao Peng; Cong-Qiang Liu (Water Research, 2023)

Minerals resource rent responses to economic performance, greener energy, and environmental policy in China: Combination of ML and ANN outputs - Fu Chen; Sunil Tiwari; Kamel Si Mohammed; Weidong Huo; Paweł Jamróz (Resources Policy, 2023)

The interaction mechanism, conformational changes and computational simulation of the interaction between surface layer protein and mannan at different pH levels - Mengqi Fu; Si Mi; Jinrong Zhao; Xianghong Wang; Jie Gao; Yaxin Sang (Food Chemistry, 2023)

The MocR family transcriptional regulator DnfR has multiple binding sites and regulates Dirammox gene transcription in Alcaligenes faecalis JQ135 - Si‐Qiong Xu; Xiao Wang; Lu Xu; Ke‐Xin Wang; Yin‐Hu Jiang; Fu‐Yin Zhang; Qing Hong; Jian He; Shuang‐Jiang Liu; Ji‐Guo Qiu (Environmental Microbiology, 2023)
Microbial ammonia oxidation is vital to the nitrogen cycle. A biological process, called Dirammox ( dir ect amm onia ox idation, NH 3 →NH 2 OH→N 2 ), has been recently identified in Alcaligenes ammonioxydans and Alcaligenes faecalis . However, its transcriptional regulatory mechanism has not yet been fully elucidated. The present study characterized a new MocR‐like transcription factor DnfR that is involved in the Dirammox process in A. faecalis strain JQ135. The entire dnf cluster was composed of 10 genes and transcribed as five transcriptional units, that is, dnfIH , dnfR , dnfG , dnfABCDE and dnfF . DnfR activates the transcription of dnfIH , dnfG and dnfABCDE genes, and represses its own transcription. The intact 1506‐bp dnfR gene was required for activation of Dirammox. Electrophoretic mobility shift assays and DNase I footprinting analyses showed that DnfR has one binding site in the dnfH ‐ dnfR intergenic region and two binding sites in the dnfG ‐ dnfA intergenic region. Three binding sites of DnfR shared a 6‐bp repeated conserved sequence 5′‐GGTCTG‐N 17 ‐GGTCTG‐3′ which was essential for the transcription of downstream target genes. Cysteine and glutamate act as possible effectors of DnfR to activate the transcription of transcriptional units of dnfG and dnfABCDE , respectively. This study provided new insights in the transcriptional regulation mechanism of Dirammox by DnfR in A. faecalis JQ135.

Hydrological regulation of nitrate sources, transformation and transport pathway in a karstic river - Cai Li; Fu-Jun Yue; Jun Zhong; Sen Xu; Si-Liang Li (Journal of Hydrology, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Stable Na-organosulfide batteries enabled by an in-situ constructed protective interphase - Chenyang Jiao; Yubing Si; Zhongju Wang; Shuai Tang; Yongzhu Fu (Chemical Engineering Journal, 2023)

Ni2P with phosphorus vacancy supported Pt clusters for efficiently electrocatalytic co-production of hydrogen and value-added chemicals from methanol-water at low potential - Xuexian Wu; Yan Zhang; Yang Yang; Guodong Fu; Fengzhan Si; Jiahui Chen; Munir Ahmad; Zhibin Zhang; Chunyi Ye; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2023)

Streptomyces Spinosirectus sp. nov., Isolated From the Medicinal Plant Xanthium Sibiricum - Yin-Feng Wang; Si-Ren Hu; Li Fu; Yan Xiao; Xin-Ke Tang; Jian Gao (Current Microbiology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Fine mapping of a stripe rust resistance gene YrZM175 in bread wheat - Jingchun Wu; Dengan Xu; Luping Fu; Ling Wu; Weihao Hao; Jihu Li; Yan Dong; Fengju Wang; Yuying Wu; Zhonghu He; Hongqi Si; Chuanxi Ma; et al. (Theoretical and Applied Genetics, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

Responses of Labile Organic Carbon and Extractable Cadmium Fractions in an Agricultural Soil Following Long-Term Repeated Application of Pig Manure and Effective Microbes - Shaocheng Si; Yuan Li; Chen Tu; Yucheng Wu; Chuancheng Fu; Shuai Yang; Yongming Luo (Bulletin of Environmental Contamination and Toxicology, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Circular RNA circ-PLCD1 functions as a tumor suppressor in non-small cell lung cancer by inactivation of PI3K/AKT signaling pathway - Jiming Si; Jianjun Jin; Jingjing Sai; Xiaoting Liu; Xiao Luo; Zhenqiang Fu; Jing Wang (Human Cell, 2022)

Field investigation and numerical simulation on rockfalls in Zhangmu Town, Tibet, China - Zhong-fu Wang; Han-dong Liu; Si-ming He; Dan Bi (Journal of Mountain Science, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

New phenolic acids from the whole herb of Elephantopus scaber Linn. and their anti-inflammatory activity - Lu Fu; Di Pei; Meng Yu; Hai Shang; Jin-Guang Si; Hong-Wu Zhang; Tao Zhang; Zhong-Mei Zou (Natural Product Research, 2021)

SUMO conjugating enzyme: a vital player of SUMO pathway in plants - Shantwana Ghimire; Xun Tang; Weigang Liu; Xue Fu; Huanhuan Zhang; Ning Zhang; Huaijun Si (Physiology and Molecular Biology of Plants, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

The protective effect of small peptides from Periplaneta americana on hydrogen peroxide–induced apoptosis of granular cells - Qin Wang; Rong Fu; Caihua Kong; Kena Liu; Huaxin Si; Shiyan Sui (In Vitro Cellular & Developmental Biology - Animal, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Engineering a heterologous synthetic pathway in Escherichia coli for efficient production of biotin - Pei-Pei Wei; Fu-Cheng Zhu; Cun-Wu Chen; Guo-Si Li (Biotechnology Letters, 2021)

Role and application of quorum sensing in anaerobic ammonium oxidation (anammox) process: A review - Quan Zhang; Nian-Si Fan; Jin-Jin Fu; Bao-Cheng Huang; Ren-Cun Jin (Critical Reviews in Environmental Science and Technology, 2021)

Formation mechanism and risk assessment of unstable rock mass at the Yumenkou tunnel entrance, Shanxi province, China - Zhong Fu Wang; Si Ming He; Han Dong Liu; Dong Dong Li (Bulletin of Engineering Geology and the Environment, 2021)

Efficient removal of antibiotic oxytetracycline from water using optimized montmorillonite-supported zero-valent iron nanocomposites - Mai Lien Tran; Si-Wei Deng; Chun-Chieh Fu; Ruey-Shin Juang (Environmental Science and Pollution Research, 2020)

Silibinin inhibits migration and invasion of breast cancer MDA-MB-231 cells through induction of mitochondrial fusion - Lingling Si; Jianing Fu; Weiwei Liu; Toshihiko Hayashi; Yuheng Nie; Kazunori Mizuno; Shunji Hattori; Hitomi Fujisaki; Satoshi Onodera; Takashi Ikejima (Molecular and Cellular Biochemistry, 2020)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Sucrose signaling function on the formation and swelling of bulblets of Lilium sargentiae E.H. Wilson - Suping Gao; Yuan Zhu; Lingyun Zhou; Xiaofeng Fu; Ting Lei; Qibing Chen; Xiaofang Yu; Yonghong Zhou; Wenji Li; Ju Hu; Di Hu; Wenhui Si (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

Development of a preliminary slope stability calculation method based on internal horizontal displacements - Hua-fu Pei; Si-qi Zhang; Lalit Borana; Bing Yuan (Journal of Mountain Science, 2018)

HAP1 Is Required for Endocytosis and Signalling of BDNF and Its Receptors in Neurons - Yoon Lim; Linda Lin-Yan Wu; Si Chen; Ying Sun; Swarna Lekha Vijayaraj; Miao Yang; Larisa Bobrovskaya; Damien Keating; Xiao-Jiang Li; Xin-Fu Zhou (Molecular Neurobiology, 2018)

Structural characterisation of a water-soluble polysaccharide from tissue-cultured Dendrobium huoshanense C.Z. Tang et S.J. Cheng - Hua-Yang Si; Nai-Fu Chen; Nai-Dong Chen; Cheng Huang; Jun Li; Hui Wang (Natural Product Research, 2018)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

The influence of urbanization on karst rivers based on nutrient concentration and nitrate dual isotopes: an example from southwestern China - Zhong-Jun Wang; Fu-Jun Yue; Jie Zeng; Si-Liang Li (Acta Geochimica, 2017)

Acute psychoactive and toxic effects of D. metel on mice explained by 1H NMR based metabolomics approach - Yonghong Fu; Zhihong Si; Pumin Li; Minghui Li; He Zhao; Lei Jiang; Yuexiao Xing; Wei Hong; Lingyu Ruan; Jun-Song Wang (Metabolic Brain Disease, 2017)

Identification of different cytoplasms based on newly developed mitotype-specific markers for marker-assisted selection breeding in Brassica napus L. - Shuangping Heng; Fengyi Chen; Chao Wei; Kaining Hu; Zonghui Yang; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Ping Si; Tingdong Fu; Jinxiong Shen (Plant Cell Reports, 2017)

Using a global reference sample set and a cropland map for area estimation in China - Le Yu; XueCao Li; CongCong Li; YuanYuan Zhao; ZhenGuo Niu; HuaBing Huang; Jie Wang; YuQi Cheng; Hui Lu; YaLi Si; ChaoQing Yu; HaoHuan Fu; et al. (Science China Earth Sciences, 2017)

Autologous Bone Marrow Mononuclear Cell Transplantation Delays Progression of Carotid Atherosclerosis in Rabbits - Kefei Cui; Xiao Ma; Lie Yu; Chao Jiang; Chao Fu; Xiaojie Fu; Xiaofang Yu; Yuanjing Huang; Suyun Hou; Caifeng Si; Zhengguang Chen; Jing Yu; et al. (Molecular Neurobiology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Mechanism of Rock Burst Occurrence in Specially Thick Coal Seam with Rock Parting - Jian-chao Wang; Fu-xing Jiang; Xiang-jun Meng; Xu-you Wang; Si-tao Zhu; Yu Feng (Rock Mechanics and Rock Engineering, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Persistence Parameter: a Reliable Measurement for Behavioral Responses of Medaka (Oryzias latipes) to Environmental Stress - Li Yin; Haitang Yang; Guiyun Si; Qing Ren; Rongshu Fu; Biao Zhang; Xu Zhang; Xiaoguang Wang; Pingping Qi; Chunlei Xia; Zongming Ren; Tae-Soo Chon; et al. (Environmental Modeling & Assessment, 2016)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Successful establishment and evaluation of a new animal model for studying the hepatitis B virus YVDD mutant - Yan-Xiu Ma; Zhi-Wei Song; Xu Teng; Li-Juan Fu; Mei-Li Hao; Si-Jia Chen; Wei-Zhen Xu; Hong-Xi Gu (Archives of Virology, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Two cotton Cys2/His2-type zinc-finger proteins, GhDi19-1 and GhDi19-2, are involved in plant response to salt/drought stress and abscisic acid signaling - Gang Li; Fu-Ju Tai; Yong Zheng; Juan Luo; Si-Ying Gong; Ze-Ting Zhang; Xue-Bao Li (Plant Molecular Biology, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease - An Zhang; Jun-ling Cao; Bo Yang; Jing-hong Chen; Zeng-tie Zhang; Si-yuan Li; Qiang Fu; Clare E. Hugnes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)

Plant regeneration of Chorispora bungeana via somatic embryogenesis - Jianhui Wang; Lizhe An; Ruoyu Wang; Daqun Yang; Jing Si; Xuanying Fu; Jianfeng Chang; Shijian Xu (In Vitro Cellular & Developmental Biology - Plant, 2006)